CONSERVAÇÃO E VALORES DAS PAISAGENS CULTURAIS MUNDIAIS: A trajetória da preservação do Conjunto Moderno da Pampulha, de patrimônio histórico e artístico nacional à paisagem cultural mundial (1947 - 2016) - Luciana Rocha Féres (2021)
The complexity of the cultural landscape typology as a dynamic system, especially in cities and metropolitan regions, brings great challenges to the field of heritage preservation, because Western conservation theories and norms have long been focused on historical and artistic values, on the attributes of authenticity and integrity, with a narrow view of cultural significance. Contemporary theories and approaches to the conservation of cultural heritage, such as the values-based theory, and the methodology proposed by the Burra Charter, which is premised on the cultural significance of places, point to possible ways to deal with the complexity of the conservation of the cultural landscape typology as heritage. In the case of cultural landscapes inscribed on the UNESCO World Heritage List, the preservation of the "outstanding universal value" should be ensured. The research investigates the concept of cultural landscape in the field of heritage, its use as a typology within the world heritage, and the various approaches to its conservation, specifically the Recommendation on the Historic Urban Landscape – HUL of the UNESCO World Heritage Center for the world heritage cultural landscapes. The research also points to perspectives for the conservation of the world heritage cultural landscapes with more flexible approaches, capable of embodying changes, and not the static conservation of the "monument city" as in the past. The case study of the Pampulha Modern Ensemble located in Belo Horizonte, Minas Gerais, Brazil, is elected. Through the study, it is intended to elucidate the process of its national and universal patrimonialization that illustrates and represents the expansion of the concept of heritage, as well as the transformations of the field of policies for the preservation of cultural heritage in Brazil, and in the World, and culminates with its inscription as a cultural landscape in the UNESCO World Heritage List (United Nations Educational, Scientific and Cultural Organization). The hypothesis presented in this research is that there is a conceptual disconnection between the candidate asset "Pampulha Modern Ensemble" presented in the nomination dossier and the site inscribed as a Cultural Landscape in the World Heritage List. The heritage site inscribed under the Cultural Landscape typology at the universal level extrapolates the candidate asset circumscribed as the "urban ensemble" of modern heritage in the nomination process. It is intended to prove this hypothesis through the critical analysis of the key documents of the process of patrimonialization of the property. The time frame of the research begins in 1947, taking as a milestone the federal listing of the Church of São Francisco de Assis by IPHAN – National Institute of Historical and Artistic Heritage, and runs until the year 2016, date of the inscription of the Pampulha Modern Ensemble in the World Heritage List. Through the analysis of the processes of listing the Pampulha Modern Ensemble at the federal, state, municipal levels and its candidacy and inscription on the World Heritage List, it is intended to reveal the various layers and temporalities - the attribution of values and meanings - superimposed on the patrimonialization of the Pampulha Modern Ensemble as a palimpsest.